Answer:
x=-2
Step-by-step explanation:
Given the system of equations:
![\begin{gathered} 2x+y=1 \\ 2x+3y=11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tb0ghelourqri7eqss5yzrsbx22huu9vzp.png)
We use the method of elimination by subtracting.
This gives us:
![\begin{gathered} -2y=-10 \\ y=(-10)/(-2) \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g3fvfqexufwucs24qo4qistw9m1m0ikbjm.png)
We then substitute y=5 into any of the equations to solve for x.
![\begin{gathered} 2x+y=1 \\ 2x+5=1 \\ 2x=1-5 \\ 2x=-4 \\ x=-(4)/(2) \\ x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pz3mlckr1czlsfm9m436by82szyttaq4ig.png)
Therefore, the value of x in the solution to the system of equations is -2.